HAKIKAT PERTANGGUNGJAWABAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN PEMERINTAHAN - Muhammad Syarif Nuh (Faculty of Law, Universitas Diponegoro, 2012)
Good governance can only be realized in state law. One of the principle of good governance is the principle of accountability which requires all local governments accountable for their actions in governance. Accountability of local government consisting of political accountability, law and economics. Political accountability, there are two kinds of common liability in the form of regional governance that must be done once a year to the central government as the basic building material evaluation and subsequent local government and governance accountability reports to Parliament and the Government in form the public governanceas a judgment to accept or reject the report of accountability that could result in dismissal of the Local Government and the tremendous responsibility that is required by Parliament in the form requesting the information reported in the local government accountability office that could result in local governments can not be nominated for the next period. Legal liability is a liability for the actions of local governments that harm the public or other parties. Divided into two legal liability personal liability, which focuses on the functional or behavioral approach may result in a severe misuse of authority in the form of maladministration and liability positions that focus on the approach to the legality (validity) regarding the use of authority, procedure and substance. Differences in personal responsibility and liability positions at the consequences of criminal, civil, and administration. Criminal liability only relates to personal responsibility, civil liability relating to both personal responsibility and accountability responsibilities and administrative positions relating to the responsibilities of office. While the economic responsibility held in conjunction with political accountability.Keywords: Government, Governance, Accountability